2009
DOI: 10.1177/1757975909339764
|View full text |Cite
|
Sign up to set email alerts
|

Work life and mental well-being: single and coupled employed mothers in Southern Europe and Scandinavia

Abstract: Many European mothers, single and coupled, combine work outside the home and family life. The effects of this on their mental well-being may vary depending on the level of support available from the State's welfare system, since welfare may buffer working mothers from some of the stress that can arise from trying to manage significant responsibilities on the job and at home. Welfare may be especially important for single working mothers, for whom the burden of multiple roles may be even heavier. The present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…When classifying living area into two categories—urban or rural—we did not find a significant association between living area and PMH. Living alone,16 33 35 low social support,13 14 16 34 39 loneliness14 and exclusion40 have been associated with poor positive mental or emotional health and a study in Russia found associations between high levels of trust and high emotional health 40. We found that not or rarely attending religious services was associated with poor PMH.…”
Section: Discussionmentioning
confidence: 50%
“…When classifying living area into two categories—urban or rural—we did not find a significant association between living area and PMH. Living alone,16 33 35 low social support,13 14 16 34 39 loneliness14 and exclusion40 have been associated with poor positive mental or emotional health and a study in Russia found associations between high levels of trust and high emotional health 40. We found that not or rarely attending religious services was associated with poor PMH.…”
Section: Discussionmentioning
confidence: 50%
“…Another important PMH need prioritized at the differential exposure level is providing proper working conditions. Given the participants’ age group in this study is defined as adulthood, giving the first two priorities to occupation-related needs at both national and community levels demonstrates the importance of employment and its related conditions in this age group ( 44 46 ). Regardless of other work conditions, work hours play an important role in PMH.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on single mothers, not fathers. Single mothers are found to have increased levels of financial stress (9,10); increased levels of psychological distress, depression, and poor self-rated health (9,(11)(12)(13); and reduced levels of subjective well-being, such as life satisfaction (14,15).…”
Section: Theoretical Backgroundmentioning
confidence: 99%